Air Pollution Exposure and Hemoglobin Levels in Fuel Station Workers: A Cross-Sectional Study on Occupational Health Risks - Zarathustra, Ath.Thaariq Lustician; Liliawanti; Mayo, Dagradi Eric; Pramita, Anindya (Perhimpunan Dokter Kedokteran Komunitas dan Kesehatan Masyarakat Indonesia (PDK3MI), 2025)
Air pollution is a recognized environmental risk factor with documented effects on hematological and immunological systems, frequently leading to reduced hemoglobin levels and the development of anemia. Hemoglobin, a crucial component of erythrocytes, facilitates oxygen and carbon dioxide transport throughout tissues. Levels below 13.5 g/dL in males and 12 g/dL in females are categorized as low. This literature review aimed to synthesize existing evidence on the role of air pollution exposure in influencing hemoglobin levels among fuel station workers. Utilizing a systematic literature search, ten relevant journal articles were identified and critically analyzed to summarize prior findings. The review consistently revealed that prolonged and continuous exposure to air pollution is likely to impair hemoglobin synthesis, leading to a decrease in hemoglobin levels among fuel station workers. In conclusion, this review demonstrates a significant role of air pollution exposure in affecting hemoglobin levels in this occupational group, highlighting a critical public health concern.